ANALISIS KETAHANAN UMUR PEMAKAIAN BAN PADA MOBIL PENUMPANG JENIS SEDANTIPE F30 DENGAN MESIN BERKAPASITAS 1998CC - Dedy Krisbianto; Arianto Herbangan Silalahi (KALPIKA, 2022)
Tires are an important part of a vehicle whose function is to reduce vibrations caused by poor road surface contours, providing stability between vehicles and road surfaces to increase acceleration and facilitate movement. Road surface texture is an important factor in providing safety and comfort for road users. One of the factors influencing the wear of tires on F30 type sedans wi th 1998cc engines is the thickness of the grooves and the treadwear indicator. The theoretical calculations made in research on tire use are done by correlating between the average speed of the vehicle, the load on the rear wheels, and the road surface to the centrifugal force, traction, and rolling resistance of the tire with a load of 2 passengers resulting in centrifugal force on tires 372, 21 kN, traction 1034.92 kN, and rolling resistance 17.59 kN. Tests performed on three different tire brands show that the faster the driving speed, the faster the tire flow erodes, the tire flow indicator or treadwear will decrease by 0.0041 mm to 0.0048 mm per hour. This proves that the test of this theoretical calculation can be a reference in average driving speed.